Faktor-Faktor Pendorong dan Penghambat Implementasi E-Monev (Studi di KPU Kabupaten Jember) - Toidin, Toidin (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The General Election Commission (KPU) is restricted by very strict and detail rules. KPU utilizes e-Monev based on Government Regulation no. 39 in 2006 on Procedures of the Control and Evaluation to monitor the implementation of the duties and financial performance to be effective and accountable since 2014. It needs to be assessed how its implementation; whether successful or failed, and to know what supporting and obstructing factors of its implementation. The implementation results showed that the implementation performance has not been suitable with its design. The political performance demonstrated the success by successfully organizing local election in 2015 which was suitable with its stages without violence. Implementation of e-Monev was supported by factors of standards and objectives and the characteristics of the agencies, while the obstructing factors were policy resources, communication between the implementing agencies; dispositions; economic, social and politic conditions.